Why Not Speak Up? A Narrative Inquiry into the Silence of Undergraduate EFL Learners in Speaking Classes - Andi Syifa Hanifaturrizkia; Aridah Aridah; Didik Sucahyo; Desy Rusmawaty; Maria Teodora Ping (Ahmad Dahlan Journal of English Studies, 2025)
Despite the importance of speaking skills in communicative English as a Foreign Language (EFL) pedagogy, many undergraduate EFL learners remain silent in speaking courses. Existing research has largely focused on silence among EFL learners in other cultural contexts, leaving a gap in understanding the sociocultural, institutional, and linguistic factors influencing Indonesian university students. This qualitative study employs narrative inquiry to explore the lived experiences of silent undergraduate EFL learners in speaking classes, allowing participants to share personal stories, emotions, and reflections on their silence. Guided by Krashen’s Second Language Acquisition theories and Saville-Troike’s ethnographic framework, the research investigates both the individual and contextual factors of silence. The findings show that silence is influenced by university pedagogical shock, engaging in a silent period and hindered by affective filters, as well as contextual factors such as hierarchical classroom dynamics, authoritarian teaching styles, group-influenced silence, disengagement due to uninteresting topics, and showing respect. This research highlights the need for more supportive and interactive speaking environments in EFL speaking classes and offers practical suggestions for teachers to help students participate more actively.